Comparison of sensors and methodologies for effective prognostics on railway turnout systems. (January 2016) - Camci, Fatih; Eker, Omer Faruk; Başkan, Saim; Konur, Savas
Railway turnout systems are one of the most important components of a railway's infrastructure. Their geographically distributed nature makes failure detection, forecasting and maintenance planning extremely important. Prognostics, forecasting the time to failure in order to achieve effective maintenance planning, has attracted increasing attention from industry and researchers in recent years. The prognostic approach has great potential to achieve reduced costs and increased availability. However, the applicability of any engineering model requires economic and practical justifications. This paper presents an analysis of different prognostic methods for railway turnout systems. Five different sensors, installed in a real turnout system used on Turkish State Railways, are individually analysed by applying various prognostic methods. This paper aims to guide practitioners on the application of prognostics and health management technologies to railway turnout systems by discussing the advantages and disadvantages of using different sensors and prognostic methods.